Chemical Content of The Didim and Kemer Meteorites - Özdemir, B.; Özel, M.E.; Yeşiltaş, M.; Yalçın, M.G. (Wiley, 2019)
Until today, a total of 16 meteorites fell in Turkey, two of which are Didim and Kemer meteorites. Didim fell in 2007 in Aydin, and Kemer fell in 2009 in Kemer. Both events are observed falls. Didim is an H3-5 ordinary chondrite, it contains H5 clasts in a H3 host [1]. Opaque phases are also present in Didim, and were investigated previously [2]. There are multiple lithologies in the Didim meteorite, such as white, gray, and dark lithologies. Initial characterization indicates an homogeneous composition for olivine and pyroxene in the white lithology (Fa19- 20, Fs17-19), however a variable composition in the darker lithology [1]. Kemer is an L4 ordinary chondrite with an homogeneous composition for olivine and pyroxene [3]. Thus far, there is no detailed information on the molecular composition of these meteorites. We studied multiple stones of the Didim and Kemer meteorites in order to obtain detailed chemical and molecular compositional information from various phases and lithologies. This information may help us constrain their parent body processes.